2016
DOI: 10.1080/15368378.2016.1194291
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields, radicals and cellular activity

Abstract: Some effects of low-intensity magnetic fields on the concentration of radicals and their influence on cellular functions are reviewed. These fields have been implicated as a potential modulator of radical recombination rates. Experimental evidence has revealed a tight coupling between cellular function and radical pair chemistry from signaling pathways to damaging oxidative processes. The effects of externally applied magnetic fields on biological systems have been extensively studied, and the observed effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In the hypothesis that free radical recombination is the basis of expected biological effects, the transition between singlet‐triplet of unpaired electron in oxygen‐based free radicals has to be considered. This transition is critical for increasing the recombination ratio of a spin‐correlated free radical pair, and is dependent on the applied MF [Barnes and Greenebaum, ; Montoya, ]. However, the reaction centers related to the expected antitumor effect are unknown, thus the lifetime of spin states and energy splitting between singlet and triplet states cannot be precisely determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothesis that free radical recombination is the basis of expected biological effects, the transition between singlet‐triplet of unpaired electron in oxygen‐based free radicals has to be considered. This transition is critical for increasing the recombination ratio of a spin‐correlated free radical pair, and is dependent on the applied MF [Barnes and Greenebaum, ; Montoya, ]. However, the reaction centers related to the expected antitumor effect are unknown, thus the lifetime of spin states and energy splitting between singlet and triplet states cannot be precisely determined.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic fields at low intensities have pronounced effects on unpaired electrons in molecules participating in chemical reactions and electron transfer processes (3,4). Pairing of electrons in bimolecular reactions and electron transfer processes with free radical intermediates, termed as the radical pair mechanism (RPM), is perturbed by magnetic fields in the milliTesla (mT) and microTesla (µT) ranges (3)(4)(5)(6). This perturbation is due to a quantum mechanical phenomenon in which the spin of an electron tends to align itself with the axis of a magnet.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have found that, in most cases, strong static magnetic fields (≥100 μT) increase ROS levels [Calabro et al, 2013; Vergallo et al, 2014; Zablotskii et al, 2014; Wang and Zhang, 2017], while HMFs significantly decrease cellular ROS levels [Martino and Castello, 2011; Zhang et al, 2017; Novikov et al, 2018; Van Huizen et al, 2019], the mechanism by which magnetic field exposure modulates ROS concentration in the cells remains unclear. Radicals are produced ubiquitously during many biological metabolic reactions, and it has been proposed that weak magnetic fields can change free radical reactions and free radical concentrations in biological systems and influence specific cellular functions [Barnes and Greenebaum, 2015; Montoya, 2017]. Free radicals are involved in the modulation of biological functions in response to HMFs, and changes in radical concentrations offer a reasonable explanation for some of the HMF‐induced biological effects.…”
Section: The Potential Mechanism Of Hmf‐induced Decrease In Cellular Rosmentioning
confidence: 99%
“…It has been proposed that weak magnetic fields can change free radical reactions and levels, and consequently influence specific cellular functions and inhibit or accelerate cell growth [Barnes and Greenebaum, 2015; Montoya, 2017]. Therefore, free radicals may represent potential molecules for modulating biological functions in response to HMFs.…”
Section: Effects Of Hmf Exposure On Animals or Cellsmentioning
confidence: 99%